2012
DOI: 10.1111/j.1464-410x.2012.11519.x
|View full text |Cite
|
Sign up to set email alerts
|

High grade prostatic intraepithelial neoplasia does not display loss of heterozygosity at the mutation locus in BRCA2 mutation carriers with aggressive prostate cancer

Abstract: What ' s known on the subject? and What does the study add?The risk of developing aggressive prostate cancer is increased for men carrying a pathogenic germline mutation in BRCA2 . An earlier study by the Kathleen Cuningham Consortium for Research into Familial Breast Cancer showed that BRCA2 mutation carriers displayed a loss of heterozygosity (LOH) within their prostate cancer tissue in the majority of cases, thus implying that the prostate cancer in these men occurred as a result of LOH for BRCA2 . High gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Similarly Edwards et al [ 37 ] identified LOH in the majority of tumors of BRCA2 mutation carriers. On the other hand, Willems-Jones et al [ 42 ] note that high-grade prostatic intraepithelial neoplasia, believed to be a precursor to prostate adenocarcinoma in some cases, does not display LOH at the mutation locus in BRCA2 mutation carriers with aggressive prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly Edwards et al [ 37 ] identified LOH in the majority of tumors of BRCA2 mutation carriers. On the other hand, Willems-Jones et al [ 42 ] note that high-grade prostatic intraepithelial neoplasia, believed to be a precursor to prostate adenocarcinoma in some cases, does not display LOH at the mutation locus in BRCA2 mutation carriers with aggressive prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of LOH has been documented using different methods in up to ∼30% of breast cancers (King et al, 2007), by NGS in ∼25% high-grade serous ovarian carcinomas (Cancer Genome Atlas, 2011), and in up to 55% of prostatic cancers associated with BRCA2 mutation carriers (Willems-Jones et al, 2012). Thus, it will be essential in future clinical trial designs to test for LOH in tumour samples to help stratify likely responders to PARP1i or similar targeted therapies.…”
Section: Brca2 Heterozygosity Suffices For Carcinogenesis: Implicatiomentioning
confidence: 99%
“…Importantly large‐scale, unbiased genomic sequencing of high‐grade serous ovarian carcinomas highlighted the retention of the wild‐type allele in end stage disease from ∼25% of germline Brca2 carriers (Atlas, 2011). Furthermore, a detailed study of prostate tumour progression in BRCA2 germline mutation carriers uncovered no LOH in high‐grade prostatic intraepithelial neoplasias, considered precursor lesions to the development of prostate adenocarcinoma, and up to 55% of the malignant tumours analysed (Willems‐Jones et al., 2012). Collectively, these data suggest that cancers arising in germline BRCA2 mutation carriers frequently fail to exhibit loss of the wildtype allele, and that failure to exhibit LOH occurs in BRCA2 ‐mutant cancers from several different tissues.…”
Section: Brca2 Tr Heterozygosity Suffices For Pancreatic Carcinogenmentioning
confidence: 99%